Evaluating phage lytic activity: from plaque assays to single-cell technologies - Panteleev, Vladimir; Kulbachinskiy, Andrey; Gelfenbein, Daria (Frontiers in Microbiology, 2025)
Bacteriophages are the most abundant biological entities on Earth, playing critical roles in microbial ecology, evolution, and horizontal gene transfer. Since the discovery of bacteriophages in the early 20th century, a wide range of techniques has been developed to study their lytic activity. This review provides a perspective on the wide range of methods for studying phage-bacteria interactions, spanning classical bulk-culture techniques and modern single-cell and high-throughput approaches. The first section covers solid culture methods relying on plaque formation phenomenon, which allow for quantification of infectious viruses, phage host-range establishment, and analysis of certain phage traits, now augmented by robotic high-throughput screening. The second section focuses on liquid culture approaches, utilizing optical density measurements, quantitative PCR, metabolic assays and cell damage assays to measure the infection dynamics. The third section details single-cell techniques, which help to dissect the heterogeneity of infection within cell populations, using microscopy, microfluidics, next-generation sequencing, and Hi-C methods. The integration of these diverse methods has greatly advanced our understanding of the molecular mechanisms of phage infection, bacterial immunity, and facilitated phage therapy development. This review is dedicated to the 110th anniversary of phage discovery and is aimed to guide researchers in selecting optimal techniques in the fast-growing field of phage biology, phage-host interactions, bacterial immunity, and phage therapy.